A condition called love. 8 - Morino, Megumi (Kodansha USA Publishing, LLC, 2024)
"As they begin their first summer break since getting together, Hotaru and Hananoi-kun vow to experience even more "firsts" together! But all their plans are derailed when Hananoi-kun's father suddenly returns from overseas! Then, Yao-kun finally acknowledges his feelings for Hotaru...just in time for the two of them to have an intimate moment at the summer festival!"--